FAKTOR-FAKTOR YANG DI PERTIMBANGKAN KONSUMEN DALAM MEMBELI PRODUK GARNIER DI DENPASAR - Stevanus Kakomore; Luh Komang Candra Dewi; I Ketut Mustika (Journal Research of Management, 2021)
This study aims to determine what factors and which factors are the most dominant considered by consumers in buying Garnier products in the city of Denpasar. The design of this study uses quantitative descriptive analysis with SPSS analysis tool version 24. This study uses 70 respondents as research samples drawn based on purposive sampling method. The research method applied in this study is based on factor analysis with data collection techniques used are interviews, documentation, and questionnaires. The results of this study indicate that only 14 independent variables can be analyzed. Of the 14 variables after the factor rotation process, there are four main components. The naming of the new factors is determined according to the variables that make up the factor. The first factor is marketing and application factors which have the highest eigenvalue of 4.688 and are able to explain the total variance of 33.487%. The second factor is the personal factor with an eigenvalue of 2,021 with a variance percentage of 14.707%. The third is a factor of excellence with an eigenvalue of 1.377 with a total variance of 9.835%. The fourth factor is the reference factor which has an eigenvalue of 1.041 with a total variance of 7.062%. Implications for the company to always maintain the quality of service and product quality they have.